FORECASTING TECHNIQUES AND APPLICATIONS - Abdul Talib Bon (Penerbit UTHM, 2005)
This book is distinctive for its attention to practical forecasting current issue s in Malaysia, its comprehensive coverage of both statistical models and neural networks models and how to implement them in practice within a modern manufacturing and business environment, and the inclusion of many recent developments in forecasting research. The book is written in a simple, straightforward style and makes extensive use real cases found from research to provide the university and college student with the necessary link between theoretical concepts and their real-world application.